Mathematical Modelling For Growth Of Aspergillus Niger Ftcc 5003 During Solid-State Fermentation On Palm Kernel Cake - Gan, Siew Hung (2005)
An attempt to obtain the first model for growth of Aspergillus niger FTCC 5003 in solid-state fermentation (SSF) using palm kernel cake (PKC) as substrate was investigated. Initially, it was found that pre-germination of fungal spores occurred after 10 hours fermentation. Hence, 10 hours after fermentation process is used to denote 0 day in the present work. Both protein and glucosamine contents were well correlated to the fungal dry weight in SSF on support material as described by the equations, whereby fungal dry weight = (protein concentration - 0.10) I 3.03 and fungal dry weight = (glucosamine concentration - 6.57) 1222.89, respectively. These equations were then used as calibration standard for indirect biomass estimation for growth of Aspergillus niger FTCC 5003 in SSF on PKC system. Estimated fungal dry weight based on protein and glucosamine concentration, PKC dry weight and Pmannanase activity were determined in the study on growth of Aspergillus niger FTCC 5003 in SSF using PKC as substrate. It was found that the relationship between PKC dry weight and estimated fungal dry weight based on protein concentration and between PKC dry weight and P-mannanase well described the growth pattern of Aspergillus niger FTCC 5003 in this system with correlation coefficient values of -0.97 and 0.97, respectively. However, the relationship between PKC and estimated fungal dry weight based on glucosamine concentration was poor as the correlation coefficient value between these two variables was - 0.30. An initial kinetic study showed that the experimental data for growth of ~ s ~ e r ~ z lnliugesr FTCC 5003 in SSF on PKC was less significant based on the Monod growth model. The study on logistic growth model found that the simulation curve fitted well to the experimental data for growth of Aspergillus niger FTCC 5003 during SSF on PKC which estimated fungal dry weight was based on protein concentration. The deviation between simulated and experimental data was not significant at significance probability of 5%. However, the simulation curve did not fit well to the experimental data for growth of Aspergillus niger FTCC 5003 in SSF on PKC which estimated fungal dry weight was based on glucosamine concentration. In the study of growth model based on p-mannanase activity, the growth model for estimated fungal dry weight based on glucosamine was not successfully determined and developed. Nevertheless, a new model was successfully obtained and proposed for the growth model based on p-mannanase activity for estimated fungal dry weight based on protein concentration. The proposed model was able to simulate the growth and reflect the actual growth profile of Aspergillus niger FTCC 5003 in SSF on PKC. Besides, the value of prob> I T I in p-mannanase activity based growth model for estimated fungal dry weight based on protein concentration (0.95) found to be closer to 1 indicating that it was able to simulate the Aspergillus niger FTCC 5003 growth profile more precisely in this system compared to logistic growth model for estimated fungal dry weight based on protein concentration which the value of prob> I T I was 0.76.